If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(t + -14) + 7(t + -12) = 14 Reorder the terms: 3(-14 + t) + 7(t + -12) = 14 (-14 * 3 + t * 3) + 7(t + -12) = 14 (-42 + 3t) + 7(t + -12) = 14 Reorder the terms: -42 + 3t + 7(-12 + t) = 14 -42 + 3t + (-12 * 7 + t * 7) = 14 -42 + 3t + (-84 + 7t) = 14 Reorder the terms: -42 + -84 + 3t + 7t = 14 Combine like terms: -42 + -84 = -126 -126 + 3t + 7t = 14 Combine like terms: 3t + 7t = 10t -126 + 10t = 14 Solving -126 + 10t = 14 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '126' to each side of the equation. -126 + 126 + 10t = 14 + 126 Combine like terms: -126 + 126 = 0 0 + 10t = 14 + 126 10t = 14 + 126 Combine like terms: 14 + 126 = 140 10t = 140 Divide each side by '10'. t = 14 Simplifying t = 14
| 12-0.8(x-4)=0.4(9x-4) | | 5(24+16)-9=-8(5y-45) | | 12x-(2x-12)=4+9x | | 11=-4x-9 | | -3p-3=-9-2p | | 2(x+4)=x+8 | | 2(x+4)=2x-8 | | 2(x+4)=x-8 | | 3(d-9)=4(d-5) | | 5x/2-x=x/10-21/5 | | 6(2z-3)+3z=22 | | 34+21= | | 6x+4x+3+8=5x+3+4x | | 6-8(a+1)=7+a | | 11111-1532= | | 4x+12=2X+2 | | (21b-9)-5(4b+1)=-7 | | 4x+12=2X+1 | | (21b-9)-5(4+1)=-7 | | 23.5a+12.5=9.3a-4.8 | | g(x)=2x^2+x-1 | | 3p-5=-8 | | =2+14+88/22*9+12-6-8 | | 2*x+18=0 | | -16k^2+8k+24=0 | | 42=-3(m+6)+m | | y^3-13y^2+40y= | | y-18=9 | | 2x^2-19x=0 | | 7=10(y-8) | | p=30x+40y | | x-3x=10 |